Ability of lactic acid bacteria to produce volatile phenols - Couto, José A. (2011)
Thirty-live strains of lactic acid bacteria (20 species) were screened for the ability to produce volatile phenols from the corresponding phenolic acids, p-coumaric and ferulic, in culture medium. The concentration of vinylphertols and ethylphenols in the growth mediuro was analyzed by gas chromatography. Results showed that 13 strains t3?%) were able to produce volatile phenols from p-coumaric acid, although only three (9%) produced 4-ethylphcnnl. the final product of the p-coumnric acid metabolic pathway. The reduction step of this pathway was only l`ound in the Lactobacillus genus: L brevis, L. cotlinoider, and L plnntnrttrrt. Seven of the eight pediococci strains studied were able to produce 4-vinylphenol but not 6-ethylphenol from p-coumaric acid. The two Oenococcus nent strains und the strain of Leuconostoc rneseitterriirler studied did ROI produce either of the two p-coumaric acid derivatives. Strains that produced volatile phenols were used in subsequent studies at lower phenolic acid con-centrations. Experiments with added 5 mgfL oi`p-cottniaric acid showed that some strains can still produce re1atively high (up to S00 ugiL) concentrations of 4-ethylphenol. The capacity of lactic acid bacteria to produce volatile phenols from l`crulic acid was much lower than its capacity to produce volatile phcrtols from pecouniaric acid.